(untitled) (Biological Sciences - PJSIR, 2005)
Seven synthetic tetrahydrobenzothieno fused pyrimidine derivatives were investigated for their antibacterial and antifungal activities. Their comparative ability to inhibit growth of bacterial species Bacillus subtilis, B. megaterium, Staphyllococcus aureus, Salmonella typhi and Escherichia coli in comparison with the commercial antibiotic brand Ampi- cillin, and of fungal species Verticillium sp., Fusarium solanae, Aspergillus sp., and Penicillium sp., in comparison with the commercial antifungal brand Nystatin is reported.